Zone-plate based nanospectroscopy with soft X-rays at the SLS - Fink, Rainer; Hub, Christian; Tzvetkov, G. (Acta Physica Polonica A, 2009)
With the advance of nanostructuring techniques and the availability of third-generation synchrotron sources, Fresnel-type zone plate optics is widely used for nanospectroscopic investigations with resolutions of several 10 nm. Whereas hard X-rays commonly use diffraction or elemental contrast (e.g. using X-ray fluorescence), soft X-rays are favored to utilize the spectroscopic contrast in the near-edge region of the absorption edge. In particular, for soft materials, the relevant C-, N- and O 1s absorption edges show distinct resonances which allow fingerprint-type chemical identification, even in water surroundings. Few selected examples from modern material science will be discussed to demonstrate that the combination of X-ray absorption spectroscopy with high spatial resolution yields new insight into the nanoscale properties of these materials.